Contemporary balloon aortic valvuloplasty: Changing indications and refined technique. Issue 7 (25th February 2020) - Dall'Ara, Gianni; Tumscitz, Carlo; Grotti, Simone; Santarelli, Andrea; Balducelli, Marco; Tarantino, Fabio; Saia, Francesco
Abstract: Even if un to improve long‐term prognosis, balloon aortic valvuloplasty (BAV) may be useful in selected patients with symptomatic severe aortic stenosis either as a bridge to surgical or transcatheter valve replacement (aortic valve replacement [AVR] or transcatheter aortic valve implantation [TAVI]) or as a triage strategy for patients with uncertain indications. International guidelines recommend BAV as: a "bridge" to AVR/TAVI, a "trial" in patients with undetermined symptoms, or a "bridge‐to‐decision" in case of comorbidities. However, in clinical practice, BAV is also used as a palliative measure to improve hemodynamics and quality of life in many patients who are excluded from AVR/TAVI. Finally, BAV is often performed during TAVI to facilitate prosthesis delivery, optimize frame expansion, or for bioprosthetic valve fracture in selected valve‐in‐valve procedures. Technical innovations, which allow for a mini‐invasive approach via transradial access and pacing delivered through the wire, have led to a decrease in complications over time. This review focuses on contemporary BAV with a specific emphasis on new indications, innovative techniques, and specific complex patient subgroups.